Die nie al te wyse Salomo - Scheffler, Eben (HTS teologiese studies, 2004)
The not-so-wise SolomonIn this article it is argued that although the mere existence of Solomon is in contention in contemporary Old Testament scholarship, a historical Solomon can be accepted. However, this Solomon differs widely from the positive image of him that abounds not only in the Bible itself, but also in general Christian thought. In this article the relevant issues concerning the historical Solomon are put on the table and it is argued that a critical stance towards Biblical and other hero figures, which searches for a balance between individual and collective interests, befits more the attitude of a mature and responsible religion (and therefore spells wisdom).